Deep-Texture: A Lightweight Wearable Ring for Shape and Texture Rendering in Virtual Reality - Sung, Youjin; Kwak, DongKyu; Kim, Taeyeon; Woo, Woontack; Yoon, Sang Ho (2024 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2024)
In this paper, we suggest a foldable device that renders the shape and texture in Virtual Reality called Deep-Texture. We devised Deep-Texture to achieve effective haptic feedback with lightweight hardware by combining the basic sensations of shape and texture. By integrating the frequency change of linear resonant actuator and 1-bar mechanism, we propose a novel haptic interaction device for immersive VR experiences. During the pilot test, the results show that it enhances realism while keeping usability. By open-sourcing Deep-Texture, we aim to empower a wider range of users to engage with and benefit from haptic technology, ultimately lowering the hurdles.